(3TQM cdjGJ GdbGfhfs - (3jYbhH Hf ESMGbs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdaUd GdChd ai JYde GdSHH hGdeQV hGdYQV ajg Cf GdSHH ai cJH GdWH gh eG chf ChdkG s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg ef aVdGA GdCWHGA hZjQge Ydi eYQaI SHH GdfJf ai GdHQGR eWdbkG hNhUhUkG ai GdBfSGf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1312s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG CQVg s
Keywords: (3GdWHs